2019
DOI: 10.1016/j.canep.2019.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Investigating tea temperature and content as risk factors for esophageal cancer in an endemic region of Western Kenya: Validation of a questionnaire and analysis of polycyclic aromatic hydrocarbon content

Abstract: Background Esophageal squamous cell carcinoma (ESCC) is common in certain areas worldwide. One area, western Kenya, has a high risk of ESCC, including many young cases (< 30 years old), but has limited prior study of potential risk factors. Thermal injury from hot food and beverages and exposure to polycyclic aromatic hydrocarbons (PAHs) have been proposed as important risk factors for ESCC in other settings. The beverage of choice in western Kenya is milky tea (chai). Methods Healthy individuals ≥18 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 42 publications
0
18
0
Order By: Relevance
“…32 However, shreds of evidence from recent studies among African populations identified statistically significant associations between the source fuels used for cooking foods, cooking places, 34 consumption of hot foods and an increased risk developing of oesophageal carcinoma. [35][36][37][38] Besides, positive associations were found between tobacco use (smoking and sniffing), alcohol drinking, 36 and SCC of the esophagus. 34 Oesophageal cancer is ranked 5th of all types of malignancies in Ethiopia following uterine, cervical, breast, and colorectal cancers.…”
Section: Introductionmentioning
confidence: 92%
“…32 However, shreds of evidence from recent studies among African populations identified statistically significant associations between the source fuels used for cooking foods, cooking places, 34 consumption of hot foods and an increased risk developing of oesophageal carcinoma. [35][36][37][38] Besides, positive associations were found between tobacco use (smoking and sniffing), alcohol drinking, 36 and SCC of the esophagus. 34 Oesophageal cancer is ranked 5th of all types of malignancies in Ethiopia following uterine, cervical, breast, and colorectal cancers.…”
Section: Introductionmentioning
confidence: 92%
“…In this region, there is an excessive consumption of extremely hot tea and rice. 17,18 In addition, another factor that should be questioned is the frequent use of the plant called qat (chat or khat; Catha edulis Forsskal). Chewed in the mouth, this herb is rich in alkaloids, does not contain nicotine, but has amphetamine-like effects, leading to a psychoactive effect.…”
Section: Dovepressmentioning
confidence: 99%
“…In African countries like Tanzania, Malawi, and Kenya, hot tea consumption, especially milk tea with a high fat content that retains heat, is quite frequent and the contribution of this custom to OSCC needs to be evaluated in the AOCC, together with other risk factors acting synergistically in this malignancy. Studies in the region described hot beverage consumption could reach over 71°C [32, 33]. Middleton et al [34] conducted a case-control study in Kenya observing that “very hot” and “hot” beverage drinkers had a 3.7- and 1.4-fold OSCC risk, respectively, when compared to “warmer” drinkers.…”
Section: Epidemiological Risk Factorsmentioning
confidence: 99%